Eye tracking and the translation process: reflections on the analysis and interpretation of eye-tracking data - Hvelplund, Kristian Tangsgaard (MonTi Monografías de Traducción e Interpretación, 2015)
Eye tracking has become increasingly popular as a quantitative research method in translation research. This paper discusses some of the major methodological issues involved in the use of eye tracking in translation research. It focuses specifically on challenges in the analysis and interpretation of eye-tracking data as reflections of cognitive processes during translation. Four types of methodological issues are discussed in the paper. The first part discusses the preparatory steps that precede the actual recording of eye-tracking data. The second part examines critically the general assumptions linking eye movements to cognitive processing in the context of translation research. The third part of the paper discusses two popular eye-tracking measures often used in translation research, fixations and pupil size, while the fourth part proposes a method to evaluate the quality of eye-tracking data.